Targeting IRG1 reverses the immunosuppressive function of tumor-associated macrophages and enhances cancer immunotherapy - Chen, Yu-Jia; Li, Guan-Nan; Li, Xian-Jing; Wei, Lin-Xing; Fu, Min-Jie; Cheng, Zhou-Li; Yang, Zhen; Zhu, Gui-Qi; Wang, Xu-Dong; Zhang, Cheng; Zhang, Jin-Ye; Sun, Yi-Ping; et al. (Science advances, 2023)
Immune-responsive gene 1 (IRG1) encodes aconitate decarboxylase (ACOD1) that catalyzes the production of itaconic acids (ITAs). The anti-inflammatory function of IRG1/ITA has been established in multiple pathogen models, but very little is known in cancer. Here, we show that IRG1 is expressed in tumor-associated macrophages (TAMs) in both human and mouse tumors. Mechanistically, tumor cells induce Irg1 expression in macrophages by activating NF-κB pathway, and ITA produced by ACOD1 inhibits TET DNA dioxygenases to dampen the expression of inflammatory genes and the infiltration of CD8 + T cells into tumor sites. Deletion of Irg1 in mice suppresses the growth of multiple tumor types and enhances the efficacy of anti–PD-(L)1 immunotherapy. Our study provides a proof of concept that ACOD1 is a potential target for immune-oncology drugs and IRG1 -deficient macrophages represent a potent cell therapy strategy for cancer treatment even in pancreatic tumors that are resistant to T cell–based immunotherapy. Targeting IRG1 skews tumor associated macrophages (TAMs) into anti-tumor mode and enhances responses to anti-PD-(L)1 immunotherapy.